On the Content and Purview of Christian Bioethics - Vanderpool, Harold Y. (Christian bioethics, 1999)
The author argues that to explore what is distinctly Christian about Christian bioethics requires clarity about what is Christian. He distinguishes between the Christian (that which can be identified as authentically Christian), Christianity (the sum of that which is authentically Christian), and ecclesiastical traditions (the historic communities of faith and practice that are predicated upon both Christian and extra-Christian tradition) to critically assess what is to be declared Christian. In addition to exploring the role of New Testament scripture in identifying the Christian, the author emphasizes the need to recognize the extent to which the content of Christianity is Hebraic and Jewish.